Seletividade de herbicidas inibidores do fotossistema II para cultivares de cana-de-açúcar - Simoes, Plinio Saulo [UNESP] (2015)
For the successful implementation of chemical weed control on sugarcane crops, the selectivity of herbicides stands out as a determining and very important factor for the correct positioning of products. Each cultivar may respond differently to the same herbicide in the same dose and the selectivity is not only determined by the presence or absence of visual phytotoxicity as there are reports of early visual injuries that did not affect the production. Herbicides with an extended residual effect in the soil are recurrently used, among which are some photosystem II inhibitors. Thus, the objective of this study was to evaluate the effects of the herbicides amicarbazone, tebuthiuron and diuron + hexazinone on the electron transport rate in photosystem II (ETR), growth, development and productivity of CTC 4, CTC 9, CTC 17 and RB867515 sugarcane cultivars. Experiments were carried out in the field and on a greenhouse for each of these cultivars. In the greenhouse, evaluations of dry mass of plants, plant phytointoxication and ETR by means of a portable fluorometer were performed, and in the field evaluations were made of number of tillers, plant height, stalk diameter, productivity, ETR and technological characteristics. In the greenhouse, the herbicide tebuthiuron caused the lowest reduction levels of ETR, photosynthetic pigments, phytotoxicity, dry weight and plant height of the different sugarcane cultivars, followed by amicarbazone, and diuron + hexazinona. The effects of herbicides in ETR, photosynthetic pigments and phytotoxicity were more intense in greenhouse than in the field for all different cultivars. The herbicides tebuthiuron, amicarbazone and diuron + hexazinoa were selective for all different cultivars, and reductions in the ETR after herbicide application did not influence the productivity and technological characteristics of sugarcane.